Answer:
-5
Step-by-step explanation:
Substituting x=4 into the equation gives a 2-step linear equation in y. It is solved by isolating the variable and making its coefficient be 1.
__
<h3>use x=4</h3>
When x=4, the equation becomes ...
-3x +9y = -57
-3(4) +9y = -57
-12 +9y = -57
<h3>solve 2-step equation</h3>
The <u>first step</u> is to "isolate" the variable term (9y) by adding the opposite of the constant that is on the same side of the equation. The result is that the variable term is by itself on one side of the equal sign.
-12 +12 +9y = -57 +12 . . . . . add the opposite of -12
9y = -45 . . . . . . . . . . . . . . simplify
The <u>second step</u> is to make the coefficient of y be 1. We do that by multiplying by its inverse, 1/9. Equivalently, we divide by 9.
(1/9)(9y) = (1/9)(-45) . . . . multiply by the inverse of 9
y = -5 . . . . . . simplify
171,008 is the correct answer,,,
Since it says ''times'', you have to change the mixed numbers into fractions which will turn the equation into 10/3 x 13/5 which = 130/15. When you turn that into a mixed number, it changes into 8 10/15 or 8 2/3.
ANSWER: 8 2/3
6= w/8
is
w= -48
that should be if not sorry DX
Answer:
![\begin{bmatrix}-2\\0 \end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7D-2%5C%5C0%20%5Cend%7Bbmatrix%7D)
Step-by-step explanation:
We have the product,
.
It is known that,
'When we multiply a scalar with a matrix, the scalar is multiplied by each element of the matrix'.
So, we get,
.
⇒ ![\begin{bmatrix}-1\times 2\\0\times 2 \end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7D-1%5Ctimes%202%5C%5C0%5Ctimes%202%20%5Cend%7Bbmatrix%7D)
⇒ ![\begin{bmatrix}-2\\0 \end{bmatrix}](https://tex.z-dn.net/?f=%5Cbegin%7Bbmatrix%7D-2%5C%5C0%20%5Cend%7Bbmatrix%7D)
So, the resulting product is
.